2020
DOI: 10.15446/av.enferm.v38n2.82838
|View full text |Cite
|
Sign up to set email alerts
|

Desejo de doar leite: relação com características maternas

Abstract: Objetivo: relacionar o desejo de doar leite materno aos aspectos sociodemográficos, clínicos e obstétricos.Materiais e métodos: estudo transversal e analítico com abordagem quantitativa, realizado com 226 mulheres durante o puerpério imediato, em um Hospital de Referência do interior do Piauí, Brasil, entre dezembro de 2016 e junho de 2018. Na estatística analítica, realizaram-se os testes de Kolmogorov-Smirnov, Qui-quadrado de Pearson, Razão de verossimilhança e o teste t Student.Resultados: a caracterização … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…A study conducted with women during immediate puerperium showed relation between receiving orientation about HM donation during prenatal care period and the wish to donate milk [18]. The prenatal consultations and groups for pregnant women are timely places to discuss the subjects of breastfeeding, breast engorgement, support in case of complications during breastfeeding, HM donation possibility, and service provided by the HMB and collection stations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted with women during immediate puerperium showed relation between receiving orientation about HM donation during prenatal care period and the wish to donate milk [18]. The prenatal consultations and groups for pregnant women are timely places to discuss the subjects of breastfeeding, breast engorgement, support in case of complications during breastfeeding, HM donation possibility, and service provided by the HMB and collection stations.…”
Section: Discussionmentioning
confidence: 99%
“…For some variables, cutoff points already established in literature were adopted, namely: "baby's birth weight," in which values below 1,500 grams (g) were considered very low weight; low birth weight, equal to or greater than 1,500 g and below 2,500 g; and adequate weight, equal to or greater than 2,500 g [24]; and; "gestational age", preterm, less than 37 weeks of gestation; term, between 37 and 41 weeks and; post-term, greater than or equal to 42 weeks [25]. For the following variables: "maternal age" [11], "lives with a partner" [9,[12][13], "maternal work" [19], "maternal parity" [9,[12][13], "prenatal service" [13,19], "delivery type" [9,[12][13]19], "smoking" [12,18] and "alcoholism" [18] the categorization we employed was utilized in studies with donor mothers of HM. For variables "child age", "donated milk amount" and "donation time", these categories were adopted in order to facilitate data analysis, as there was information in registration form frequently recorded in different and non-standard ways.…”
Section: E T H O D Smentioning
confidence: 99%
See 1 more Smart Citation
“…Among the benefits of breastfeeding, we can mention the improvement of the baby’s development ( 4 ) , the reduction of the risk of infant mortality, the increased protection against infectious and chronic diseases, hydration, and strengthening of the emotional bonds in the mother-baby binomial ( 5 ) . In this regard, adequate maternal guidance regarding the advantages of breastfeeding constitutes an important strategy for strengthening this practice.…”
Section: Introductionmentioning
confidence: 99%
“…Entre os benefícios do aleitamento materno, pode-se citar a melhoria do desenvolvimento do bebê (4) , redução do risco de mortalidade infantil, aumento da proteção contra doenças infecciosas e crônicas, hidratação e fortalecimento dos laços afetivos entre o binômio mãe-bebê (5) . Nesse sentido, a adequada orientação materna em relação às vantagens da amamentação configura importante estratégia para o fortalecimento dessa prática.…”
Section: Introductionunclassified